Aplikasi Pupuk Organik Diperkaya Mikrobia Pada Usaha Pembibitan Tanaman - Mujiyo Mujiyo; Sumarno Sumarno; Suryono Suryono; Novi Rahmawati Sutopo (PRIMA: Journal of Community Empowering and Services, 2018)
Micro small business (UKM: in indonesian) "Sejahtera" is a chicken farm that has problems with chicken manure that has not been utilized properly. The farmer group "Bejo Agro Farm" is a plant nursery located in Mojogedang District, Karanganyar Regency. Availability of soil nutrients is one of the determinant factors of the quality of plant seeds. Availability of nutrients for plants can be obtained by applying organic fertilizers. Applications of microbial enriched organic fertilizers can be used as an alternative to maintain plant quality. Microbial enriched organic fertilizers contain several types of microbes that can support plant growth. Organic fertilizer comes from chicken manure coupled with several bio-starter containing beneficial microbes. The organic fertilizer used has been tested for its quality, to determine the content of the nutrient. The technology in the form of microbial enriched organic fertilizer can help "Bejo Agro Farm" to maintain the quality of plant seeds and be able to solve the problems of chicken manure waste of "Sejahtera" chicken farms.